2006
DOI: 10.1021/ja0628654
|View full text |Cite
|
Sign up to set email alerts
|

Cold Denaturation of Encapsulated Ubiquitin

Abstract: Theoretical considerations suggest that protein cold denaturation can potentially provide a means to explore the cooperative substructure of proteins. Protein cold denaturation is generally predicted to occur well-below the freezing point of water. Here NMR spectroscopy of ubiquitin encapsulated in reverse micelles dissolved in low viscosity alkanes is used to follow cold-induced unfolding to temperatures below −25 °C. Comparison of cold-induced structural transitions in a variety of reverse micelle-buffer sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 18 publications
3
62
1
Order By: Relevance
“…Ubiquitin cold denaturation has been previously studied by the groups of Wand,66 and Flynn. 67,68 Under low excess salt concentration, which are the condition of our self-assembly simulations, it is observed that denaturation is non-cooperative, multistate, with resonances corresponding to residues that make up the I44 face are lost, while resonances corresponding to the opposite face remained. [66][67][68] In Fig.…”
Section: E Interactions Of Ubiquitin With Aotsmentioning
confidence: 75%
See 1 more Smart Citation
“…Ubiquitin cold denaturation has been previously studied by the groups of Wand,66 and Flynn. 67,68 Under low excess salt concentration, which are the condition of our self-assembly simulations, it is observed that denaturation is non-cooperative, multistate, with resonances corresponding to residues that make up the I44 face are lost, while resonances corresponding to the opposite face remained. [66][67][68] In Fig.…”
Section: E Interactions Of Ubiquitin With Aotsmentioning
confidence: 75%
“…Under slightly varying conditions of pH and temperature and in a timescale appropriate for folding/unfolding dynamics, the interactions between the protein and surfactant may lead to unfolding, as seen in the non-cooperative cold denaturation of ubiquitin in RM. [66][67][68] Our simulation studies presented here provide a detailed atomic description of the structure and dynamics of a protein-RM system. The results and findings presented can serve to guide future studies on protein-RM system.…”
Section: Discussionmentioning
confidence: 99%
“…In order to gain preliminary insights into the higher susceptibility of Yfh1 to cold denaturing conditions, we compared its nanosecond timescale behavior with that of Ubiquitin (Ubq) at T c . Ubq is known to display high thermal stability 87 and to cold denature at temperatures as low as 238 K. 23 Visual inspection of snapshots of Ubq from simulations produced at T s (292 K) and T c (268 K), presented in Figures 8(a) and 8(b), respectively, indicate that the structural integrity of this protein is maintained at T c . Contrary to the structural effects in Yfh1, the beta strands of Ubq are mostly found to be nearly intact at T c .…”
Section: E Behavior Of a Thermally Stable Protein At T Cmentioning
confidence: 98%
“…19 It has been suggested that the thermodynamic advantage in terms of translational entropy gain of water molecules associated with the large decrease in solvent accessible surface area during folding is lost at lower temperatures. 20,21 Further, although cold denaturation has been largely considered to be non-cooperative, 22,23 recent NMR experiments showing similar structural loss at distal sites 24 suggest that there may be exceptions. We also mention here that cold protein denaturation is analogous to polymer unfolding resulting from hydrophobic hydration.…”
Section: Introductionmentioning
confidence: 99%
“…The populations of nonnative conformational states can be enhanced by changing the temperature, pressure, or pH, or by adding alcohol cosolvents. A cold-denaturation study by Wand et al (41,42) shows for reverse micelle-encapsulated ubiquitin that the mixed ␤-sheet is progressively destabilized from the C-terminal side in the temperature range from Ϫ20°to Ϫ30°C. In an NMR study by Cordier and Grzesiek (43), the change in hydrogen bond strength with increasing temperature was measured.…”
Section: Ubiquitin Unfolding Kinetics Under Equilibrium Conditions Rementioning
confidence: 99%